2021
DOI: 10.3390/soilsystems5010020
|View full text |Cite
|
Sign up to set email alerts
|

Antimony (V) Adsorption at the Hematite–Water Interface: A Macroscopic and In Situ ATR-FTIR Study

Abstract: The environmental mobility of antimony (Sb) is largely unexplored in geochemical environments. Iron oxide minerals are considered major sinks for Sb. Among the different oxidation states of Sb, (+) V is found more commonly in a wide redox range. Despite many adsorption studies of Sb (V) with various iron oxide minerals, detailed research on the adsorption mechanism of Sb (V) on hematite using macroscopic, spectroscopic, and surface complexation modeling is rare. Thus, the main objective of our study is to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Therefore, the amount of Sb adsorbed on each oxide under acidic conditions is greater than under basic conditions. A similar observation was made for Sb on Fh, Goe, and Hem in previous adsorption edge studies. , …”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, the amount of Sb adsorbed on each oxide under acidic conditions is greater than under basic conditions. A similar observation was made for Sb on Fh, Goe, and Hem in previous adsorption edge studies. , …”
Section: Resultssupporting
confidence: 88%
“…Previous studies using crystal truncation rod X-ray diffraction report similar results for Sb and Hem at pH 5.5 . However, Mierzwa et al demonstrate inner- and outer-sphere complexation at pH 5–7 yet only outer-sphere complexation at pH 8 using attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy and surface complexation modeling. This differs from our results under alkaline conditions, likely due to the different Sb/Fe molar ratios and characterization methods.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…An extremely sharp band was seen at 572 cm −1 for FT‐IR spectra of both the nano linear dextrin (a) and Fe 3 O 4 @NLD (b), corresponding to stretching vibrations of the Fe−O bond, suggesting a reaction between nano linear dextrin and magnetic Fe 3 O 4 nanoparticles [12a] . An extremely sharp band was seen at 640 cm −1 for FT‐IR spectra corresponding to stretching vibrations of the Sb−O bond, suggesting a reaction between magnetic nano linear dextrin and antimony [30] …”
Section: Discussionmentioning
confidence: 96%
“…The use of hematite to remove oxyanions is well documented [76]. This mineral very effectively forms surface complexes with oxyanions of As 5+ and As 3+ [77][78][79], Cr 6+ and Cr 3+ [80][81][82], U 6+ [83], Sb 5+ [84], and Se 4+ [85] which is most often favoured by an acidic environment. Importantly, it has been shown that natural minerals containing hematite have a similar ability to remove arsenic as their synthetic analogues [79].…”
Section: Potential Use Of Tuffs In Environmental Technologymentioning
confidence: 99%